2019
DOI: 10.5194/hess-2018-584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic comparison of five machine-learning methods in classification and interpolation of soil particle size fractions using different transformed data

Abstract: Abstract. Soil texture and soil particle size fractions (psf) play an increasing role in physical, chemical and hydrological processes. Digital soil mapping using machine-learning methods was widely applied to generate more detailed prediction of qualitative or quantitative outputs than traditional soil-mapping methods in soil science. As compositional data, interpolation of soil psf combined with log ratio approaches was developed to improve the prediction accuracy, which also can be used to indirectly derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To reduce subjective interpretation and to maintain constant standards, there is a need to develop new interpretation methods or tools. Machine learning or artificial intelligence has been used for graphical interpretation or target detection in various disciplines of earth science (Arabameri et al, 2020;Nanda et al, 2020;Rizvi et al, 2019;Saha et al, 2020;Zhang and Shi, 2020;Zhou et al, 2019). The machine learning may be used to facilitate the interpretation of TDR waveforms in order to determine a variety of physical properties and processes in porous media.…”
Section: Uncertainties In Graphical Interpretationsmentioning
confidence: 99%
“…To reduce subjective interpretation and to maintain constant standards, there is a need to develop new interpretation methods or tools. Machine learning or artificial intelligence has been used for graphical interpretation or target detection in various disciplines of earth science (Arabameri et al, 2020;Nanda et al, 2020;Rizvi et al, 2019;Saha et al, 2020;Zhang and Shi, 2020;Zhou et al, 2019). The machine learning may be used to facilitate the interpretation of TDR waveforms in order to determine a variety of physical properties and processes in porous media.…”
Section: Uncertainties In Graphical Interpretationsmentioning
confidence: 99%
“…Different machine learning models were adopted by researchers for the prediction of textural classes. The most common models are support vector machine (Gomez et al, 2019;Wu et al, 2018;Zhang & Shi, 2019), k-nearest neighbour (Zhang & Shi, 2019), multinomial logistic regression (Camera et al, 2017), extreme gradient boosting (Zhang & Shi, 2019), artificial neural networks (Bagheri Bodaghabadi et al, 2015;Taalab et al, 2015) and random forest model (Camera et al, 2017;Ramcharan et al, 2018). Hengl et al (2017) reported that random forest and gradient boosting outperformed other linear models in the prediction of soil texture fractions for large data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Gomes et al [41] found that the RF model was superior to Cubist in SOC mapping in Brazil while Sorenson et al [54] reported that Cubist performed better than RF in SOC prediction. Although these studies have different comparison results, other digital soil mapping studies in the HRB have also found that the prediction performance of RF models was better than SVM [55,56]. Based on these results, no single machine learning technique is most suitable for all landscapes.…”
Section: Model Performancementioning
confidence: 94%